TIDAL FLOOD MAPPING MODEL IN NORTH MEDAN REGION USING ORDINAL LOGISTIC REGRESSION AND GIS (Geographical Information System) - Kurniawan Temas Mico Arita; Ahmad Perwira Mulia; Zaid Perdana Nasution (Bulletin of Engineering Science, Technology and Industry, 2025)
Tidal floods are a regular threat in the coastal area of North Medan, which includes Medan Belawan, Medan Labuhan, and Medan Marelan. This research aims to map the level of vulnerability to tidal flooding using the Ordinal Logistic Regression (RLO) approach combined with Geographic Information Systems (GIS). Nine factors were analyzed: rainfall, drainage density, land use, distance from rivers, distance from the sea, soil type, elevation, slope, and topographic aspects. The analysis showed that rainfall, elevation, and distance from the sea were the most significant factors. The vulnerability map shows that 7.6% of areas are classified as highly vulnerable, 64.74% high, 27.36% medium, and only 0.3% low. The accuracy of the model reached 87.84%. These results provide a solid foundation for spatial planning, disaster mitigation, and coastal adaptation strategies.